CuO and ZnO nanoparticles drive the propagation of antibiotic resistance genes during sludge anaerobic digestion: possible role of stimulated signal transduction. Issue 2 (2nd January 2019) - Huang, Haining; Chen, Yinguang; Yang, Shouye; Zheng, Xiong
Abstract : CuO and ZnO NPs benefit ARG propagation by stimulating signal transduction in sludge bacteria. Abstract : Emerging contaminants, such as engineered metal oxide nanoparticles (NPs) and antibiotic resistance genes (ARGs), were reported to be accumulated in waste activated sludge. In this study, the potential impacts of CuO and ZnO NPs on the fate of ARGs during sludge anaerobic digestion were assessed. Metagenomic results showed that the presence of CuO or ZnO NPs increased ARG abundance but had no significant effects on the percentages of resistance mechanisms and types. Further functional analysis of the metagenomes revealed that signal transduction was stimulated by both NPs, especially two-component regulatory systems (TCRS) responsible for quorum sensing (QS), pili synthesis and metal tolerance. Moreover, it was found that the activated QS was closely associated with the shifted bacterial communities, especially enriched genera, such as Acidovorax, Burkholderia, Pseudomonas and Rhodobacter, which were not only the producers of QS signals but also the hosts of ARGs. Meanwhile, the triggered pili synthesis, combined with the increased abundance of mobile genetic elements (plasmids, integrons and insertion sequences), would facilitate the transfer of ARGs among diverse bacteria. Furthermore, the induced resistance to copper/zinc and other metals, such as mercury and arsenic, probably promoted the co-selection between metal and antibiotic resistance. The above results indicated that the propagation of ARGs in digesters might be driven by the NP-stimulated signal transduction. These findings may bring new insights into the understanding of ARG responses to diverse environmental stimuli.